1994
DOI: 10.1093/nar/22.4.597
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the SIP3 protein identified in a two-hybrid screen for interaction with the SNF1 protein kinase

Abstract: The Saccharomyces cerevisiae SIP3 gene was identified in a two-hybrid screen for proteins that interact in vivo with the SNF1 protein kinase, which is necessary for release of glucose repression. We showed that the C-terminal part of SIP3, recovered through its ability to interact with SNF1, strongly activates transcription when tethered to DNA. We have cloned and sequenced the entire SIP3 gene. The predicted 142-kD SIP3 protein contains a putative leucine zipper motif located in its C terminus. The native SIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Using a yeast proteome chip, some glycolytic enzymes and glucose transporters were observed to bind phosphoinositides (Zhu et al 2001), consistent with independent reports that most glycolytic enzymes are localized to the cell wall (in addition to the cytoplasm) (Hubbard et al 1994;Lesage et al 1994;Delgado et al 2001;Honigberg and Purnapatre 2003;Willis et al 2003;Young et al 2003). Other work has shown that glucose stimulates cleavage and subsequent signal transduction by the phosphoinositide PI(4,5)P 2 , as well as transcription of INM1 [which encodes a PI(4,5)P 2 biosynthetic enzyme] (Murray and Greenberg 2000).…”
Section: Analysis Of Module Coregulation With Respect To Individual Tsupporting
confidence: 86%
“…Using a yeast proteome chip, some glycolytic enzymes and glucose transporters were observed to bind phosphoinositides (Zhu et al 2001), consistent with independent reports that most glycolytic enzymes are localized to the cell wall (in addition to the cytoplasm) (Hubbard et al 1994;Lesage et al 1994;Delgado et al 2001;Honigberg and Purnapatre 2003;Willis et al 2003;Young et al 2003). Other work has shown that glucose stimulates cleavage and subsequent signal transduction by the phosphoinositide PI(4,5)P 2 , as well as transcription of INM1 [which encodes a PI(4,5)P 2 biosynthetic enzyme] (Murray and Greenberg 2000).…”
Section: Analysis Of Module Coregulation With Respect To Individual Tsupporting
confidence: 86%
“…The promoters that are activated by Sip4 remain to be identified. Genetic evidence also supports the idea of a functional relationship between Sip3 and the SNF1 pathway (134). DNA-bound LexA-Sip3 fusion proteins activate transcription of a reporter gene, which suggests that Sip3 acts downstream of Snf1.…”
Section: Targets Of Yeast Snf1mentioning
confidence: 52%
“…SIP3 AND SIP4 Other potential targets for the SNF1 complex include Sip3 and Sip4, which were identified in two-hybrid screens using Snf1 as bait (49,134,135). The interaction of Sip4 with the kinase complex is mediated by Gal83 (Vincent and M Carlson, unpublished data).…”
Section: Targets Of Yeast Snf1mentioning
confidence: 99%
“…1). To disrupt GIP1 at the chromosomal locus, we first constructed pJT26-HIS by inserting the BamHI fragment from pPL3.1 (46) carrying the HIS3 gene. The BamHI site lies at codon 31 of GIP1.…”
Section: Methodsmentioning
confidence: 99%